Cyffer, Ebermann & Ziegelmeyer (Eds.) 2009. Negation Patterns in West African Languages - Pasch, Helma (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
Norbert Cyffer, Erwin Ebermann & Georg Ziegelmeyer (Eds.) 2009. Negation Patterns in West African Languages. Typological Studies in Language 87. Amsterdam and Philadelphia: John Benjamins. 11 maps, numerous tables. Hardbound, ISBN 978 90 272 0668 8 / EUR 105 / USD 158